Collar cat temperature detector / Muhammad Hazim Waffa Zulkarnain Waffa … [et al.] - Zulkarnain Waffa, Muhammad Hazim Waffa; Jamil, Muhammad Fairuz; Mohd Yusari, Nurul Aini; Mohd Shohaimi, Nur Azlin Natasha; Bakhtiar, Badrul Izdham (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Collar cat temperature detector is a novel product concept based on the collar of a cat. For the purpose of this new product, there are two aims. First and foremost, we must ensure that our cat is stay healthy. Since we live in such a chaotic world, the second goal is to keep an eye on the owner's cat. As a result, the owner will know whether their cat is unwell whenever and wherever they are in this circumstance. Collar cat, heat sensor, LED light and transformer, and USB charging port are among the raw components used to create this product. This device will tell you if your cat is healthy or if it has a fever. The temperature of the cat's body can be used to detect it. A cat's normal temperature ranges from 38.1°C to 39.2°C; if their body temperature surpasses 39.2°C, they will develop a fever. If the cat develops a fever, the red light will turn on. This symptom indicates that the cat is not in excellent health. The cat's body is actually fighting viruses or germs when it has a fever. Heat stroke, diarrhea, food poisoning, and other illnesses might affect the cat. The owner should immediately take the cat to the veterinarian. With a low price of RM30, this product is accessible to people from all walks of life. This innovative device has the potential to save the lives of many cats, particularly imported cats (cat breeds) such as the Maine Coon, Ashera, Selkirk Rex, Siberian, and others.